Rehabilitation in the internet age: The Google-effect and the disclosure of criminal records. (September 2017) - Stacey, Christopher
The Rehabilitation of Offenders Act 1974 provides people with criminal records protection from discrimination once their criminal record becomes 'spent'. In this article, I highlight how media reports are increasingly available online and often mean spent convictions continue to be accessible to employers and others. However, I also look at a landmark case in 2014 that established a 'right to be forgotten', which enables people to ask for search results to be delisted from internet search engines. I examine to what extent this helps people with convictions.